Aspiration thrombectomy versus stent retriever thrombectomy as a first-line approach for cardiogenic cerebral embolism and cryptogenic stroke in large vessels of the anterior circulation - Zhiqiang, Peng; Junchen, Chen; Wenying, Cao; Dongqing, Zhao; Mi, Ma; Qiaowei, Li; Zhenzhen, Zhu; Wanyi, He; Biqing, Yang; Minqi, Cao (Frontiers in Neurology, 2024)
This study aims to compare the clinical efficacy of aspiration thrombectomy and stent retriever thrombectomy as first-line approach for anterior circulation large vessel cardiogenic cerebral embolism and cyptogenic stroke.This retrospective observational study included patients with anterior circulation large vessel cardiogenic cerebral embolism and cyptogenic stroke treated with endovascular therapy. Patients were grouped according to the first-line approach they received: aspiration thrombectomy or stent retriever thrombectomy. The primary outcome measure was the change in National Institute of Health Stroke Scale (NIHSS) score from preoperative to immediate postoperative and from preoperative to discharge. Secondary indicators included the rate of favorable prognosis at discharge [Modified Rankin Scale (mRS) score ≤2], successful vessel recanalization rate [modified Treatment in Cerebral Ischemia (mTICI) score ≥ 2b], time from successful femoral artery puncture to successful vessel recanalization, perioperative complications.The study included 127 cases, with 1 case withdrawals after enrollment due to stroke of other determined cause, with 83 in the aspiration thrombectomy group and 43 cases in the stent retriever thrombectomy group. The change in NIHSS score from preoperative to immediate postoperative was 5(1,8) in the aspiration thrombectomy group and 1(0,4.5) in the stent retriever thrombectomy group. The change from preoperative to discharge was 8 (5,12) in the aspiration thrombectomy group and 4(0,9) in the stent retriever thrombectomy group.The aspiration thrombectomy group exhibited significantly better good prognosis rates and shorter time from successful femoral artery puncture to successful vessel recanalization.There were no significant differences between the two groups in terms of successful vessel recanalization rates and perioperative complications.As first-line approach for anterior circulation large vessel cardiogenic cerebral embolism and cyptogenic stroke, aspiration thrombectomy leads to better improvement in neurological functional deficits and prognosis rates compared to stent retriever thrombectomy.Aspiration thrombectomy•S tent retriever thrombectomy•A cute large vessel occlusion stroke•A nterior circulation•C ardiogenic cerebral embolism• cyptogenic stroke